Ochratoxin A and AFM1 in Cheese and Cheese Substitutes: LC-MS/MS Method Validation, Natural Occurrence, and Risk Assessment - María Agustina Pavicich; Stefano Compagnoni; Celine Meerpoel; Katleen Raes; Sarah De Saeger (Toxins)
Cheese is vulnerable to contamination with mycotoxins, particularly ochratoxin A (OTA) and aflatoxin M1 (AFM1). This study aims to develop and validate an analytical method for the detection and quantification of OTA and AFM1 in cheese and to assess their prevalence and associated risks. A liquid chromatography–tandem mass spectrometry (LC-MS/MS) method was validated for detecting these mycotoxins in 41 cheese samples, including firm-ripened, spreadable, and plant-based alternatives. The results showed that OTA was detected exclusively in grated Parmigiano Reggiano cheese, while AFM1 was found in both Parmigiano Reggiano and Pecorino cheeses. This study goes beyond analytical method development by providing a preliminary exposure assessment and risk characterization for OTA and AFM1 in cheese, bridging the gap between analytical chemistry and public health implications. This study identified potential health risks associated with OTA, particularly for children and adolescents categorized as high consumers of Parmigiano Reggiano cheese. The findings underscore the need for monitoring of OTA and AFM1 in cheese and further research to establish regulatory limits for these contaminants.